2014
DOI: 10.1159/000357356
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of CD44-Positive Glomerular Parietal Epithelial Cells Reflects Podocyte Injury in Adriamycin Nephropathy

Abstract: Background/Aims: Recent study suggests that activation of parietal epithelial cells (PECs) contributes to pathogenesis of glomerulosclerosis and the activation marker CD44 increases in evolving glomerulosclerosis. Here we examined the pathogenic roles of CD44+ epithelial cells in mouse adriamycin nephropathy (ADRN), a representative rodent model for idiopathic focal segmental glomerulosclerosis (FSGS). We also evaluated whether the prevalence of CD44+ PECs reflects different levels of podocyte injuries. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 48 publications
3
27
0
Order By: Relevance
“…The CD44-positive PECs appeared prior to glomerulosclerosis and formed a bridge from Bowman's capsule to the capillary tuft; within this bridge, there was decreased expression of podocyte markers. These results suggested that CD44-positive PECs play a significant role in FSGS formation during CNI-induced nephrotoxicity, and previous reports have shown that they contribute to other pathophysiological form of FSGS [8,10,[20][21][22].…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The CD44-positive PECs appeared prior to glomerulosclerosis and formed a bridge from Bowman's capsule to the capillary tuft; within this bridge, there was decreased expression of podocyte markers. These results suggested that CD44-positive PECs play a significant role in FSGS formation during CNI-induced nephrotoxicity, and previous reports have shown that they contribute to other pathophysiological form of FSGS [8,10,[20][21][22].…”
Section: Discussionsupporting
confidence: 73%
“…To date, various studies have addressed the relationship between podocyte injury and PEC dynamics [8][9][10][22][23][24]. For instance, in one investigation involving patients with collapsing glomerulopathy, hyperplastic and hypertrophic epithelial cells were frequently connected to PECs and collapsed glomerular basement membranes [23].…”
Section: Discussionmentioning
confidence: 99%
“…1a, upper panels) [1,7], we investigated the expression of other markers including p-ERK, CXCR4 and AT1 in renal tissues of ADR mice by immunohistochemistry (fig. 1b).…”
Section: Resultsmentioning
confidence: 99%
“…We previously reported CD44 as a useful marker to detect PEC activation, reflecting progressive podocyte loss in ADR mice [7]. In this study, we further examined IHC expression of other proteins reported as PEC markers in several studies, CXCR4, AT1 and p-ERK [23,26,27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation